Governance Architecture of Free Nutritious Meal Programs: A Systematic Review on Policy Design and Control Systems - Octohariyanto, Ekasakti; Ayuningtyas, Dumilah; As Siddiq M Irzal, Mufti; Hardiyanti, Anggie; Nusaiba, Salma (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Introduction: Free nutritious meal programs or similar school meal programs are important interventions to improve children’s nutrition, education, and social protection. However, successful implementation largely depends on governance quality. This study aimed to synthesize governance practices of school feeding programs across countries as evidence for the development of Indonesia’s Free Nutritious Meal Program (MBG). Methods: A systematic review approach following the PRISMA 2020 guideline. Literature searches were conducted on governance studies related to MBG or similar programs across Africa, the Americas, Asia, and Europe. Quality assessment was performed using CASP and AGREE II, followed by narrative synthesis based on governance dimensions. Results: A total of 34 studies were included, comprising 12 studies from Africa, 10 from the Americas, 7 from Asia, and 5 from Europe. Of these, 21 were rated as high quality, 11 as moderate, and 2 as low quality based on CASP/AGREE II appraisal. Countries with stronger governance systems such as Brazil, Finland, Japan, Thailand, and South Africa demonstrated clearer national regulations, integrated monitoring systems, and stronger cross-sector coordination. In contrast, countries with weaker governance faced challenges related to accountability, supervision, and local implementation capacity. Hybrid governance combining strong national regulation and community ownership was identified as the most effective model for program sustainability. Conclusion: The success of MBG or similar school meal programs is strongly influenced by governance quality, accountability systems, and local institutional capacity. Strengthening regulations, digital monitoring, and cross-sector coordination are essential for improving MBG governance in Indonesia. Protocol Registration: PROSPERO CRD420261395331